2023
DOI: 10.3390/sym15091679
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Identifying Patterns Using Unsupervised Clustering Algorithms: A Data Mining Perspective

Mahnoor Chaudhry,
Imran Shafi,
Mahnoor Mahnoor
et al.

Abstract: Data mining is an analytical approach that contributes to achieving a solution to many problems by extracting previously unknown, fascinating, nontrivial, and potentially valuable information from massive datasets. Clustering in data mining is used for splitting or segmenting data items/points into meaningful groups and clusters by grouping the items that are near to each other based on certain statistics. This paper covers various elements of clustering, such as algorithmic methodologies, applications, cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…Afterward, unnecessary labels or information that could disrupt the data mining process are removed [21]. 2) Data Integration, the next stage involves data integration, where data that is separated into multiple tables is merged into one [22]. 3) Data Selection, the subsequent stage is data selection, where data or attributes needed for analysis and data mining are chosen.…”
Section: Data Processing Methodsmentioning
confidence: 99%
“…Afterward, unnecessary labels or information that could disrupt the data mining process are removed [21]. 2) Data Integration, the next stage involves data integration, where data that is separated into multiple tables is merged into one [22]. 3) Data Selection, the subsequent stage is data selection, where data or attributes needed for analysis and data mining are chosen.…”
Section: Data Processing Methodsmentioning
confidence: 99%
“…Unsupervised methods, such as clustering algorithms (e.g., k-means or DBSCAN), can identify patterns and group similar data points without prior labels. These groups can then be used as input for supervised learning models like neural networks or decision trees, which further refine the detection process by learning from labeled data [78,79]. This combination allows the system to benefit from the exploratory nature of unsupervised learning while harnessing the accuracy of supervised learning [80].…”
Section: Hybrid Approachesmentioning
confidence: 99%
“…Ezugwu et al [7] and Saxena et al [8] reported that clustering techniques can be divided into two major categories, namely, hierarchical clustering algorithms and partition clustering algorithms. More clustering categories, including grid clustering, density clustering, and model clustering, were proposed by Chaudhry et al [9] and Oyewole and Thopil [10]. K-means and hierarchical clustering techniques are the most widely used algorithms in the literature.…”
Section: Clustering Techniques and Applications For Medical Data Anal...mentioning
confidence: 99%
“…It can be observed that most studies dealt with a single disease, and K-means was commonly used as a popular clustering technique for analyzing medical data. The clustering approaches can be generally classified into categories: hierarchical clustering algorithms and partition clustering algorithms [7][8][9][10]. This study employed four clustering methods, K-means (KM), hierarchical clustering (HC), the K-means autoencoder (AEKM), and the K-means self-organizing map (SOMKM), to analyze medical data.…”
Section: Clustering Techniques and Applications For Medical Data Anal...mentioning
confidence: 99%